Ultrawide-band synthetic aperture radar for detection of unexploded ordnance modeling and measurements. - Sullivan, A.
Electromagnetic (EM) scattering from subsurface unexploded ordnance (UXO) is investigated both theoretically and experimentally. Three EM models are considered: the multilevel fast multipole algorithm (MLFMA), the method of moments (MoM), and physical optics (PO). The relative accuracy of these models is compared for several scattering scenarios. Moreover, the model results are compared to data measured by an experimental synthetic aperture radar (SAR) system, SAR images have been generated for subsurface UXO targets, in particular 155-mm shells. We compare SAR images from the measured data with theoretical images produced by the MoM and PO simulations, using a standard back-projection imaging technique. In addition to such comparisons with measurement, we consider additional buried-UXO scattering scenarios to better understand the underlying wave phenomenology
Keywords: EM models; EM scattering; MoM simulation; PO simulation; SAR images; Sommerfeld integrals; Back-projection imaging; Combined-field integral equation; Dyadic Green's function; Electromagnetic scattering; Experimental SAR system; Lossy dispersive soil; Measured data; Method of moments; Model accuracy; Multilevel fast multipole algorithm; Physical optics; Shells; Subsurface unexploded ordnance; Triangular-patch basis functions; Ultrawide-band synthetic aperture radar; Unexploded ordnance detection